PROBLEMS OF STABILITY OF LINEAR NON-STATIONARY SYSTEMS ON A FINITE TIME INTERVAL - Dalbekova, К.С; Gusmanova, Ф.Р; Berkimbaeva, С.Б; Iskakova, А.К (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
When studying various processes taking place in real life, we have to deal with one of the most important concepts - the concept of stability of movement. The foundations of the theory of stability of motion were developed at the end of the last century by the great Russian scientist A. M. Lyapunov. As is known, Lyapunov stability is considered on an infinite time interval, which is a serious obstacle for many applications, since most of the objects of research function for a finite period of time. The concept of stability, introduced for an unlimited period of time, cannot be used to evaluate the properties of motion within a finite period of time. The study of motion stability by analyzing solutions of the corresponding equations is permissible and makes sense only if the mathematical model of physical reality is fully adequate. The purpose of this work is to study the stability and stabilization of the motion of linear non-stationary systems.